2021
DOI: 10.3389/fpsyt.2021.634080
|View full text |Cite
|
Sign up to set email alerts
|

Supported Employment, Participation at Work, and Peer Support: A Qualitative, Participatory Case Study Report of the Geesthacht Model

Abstract: Background: For people who have experienced mental health crises or psychosocial disabilities, it is considerably more difficult to receive support to participate in work on an equal basis with others. In the town of Geesthacht, in Northern Germany, an integrative care network was implemented that allows for acute psychiatric treatment as well as participation in work and activities. This paper aims to explore the principles, advantages, and challenges of this innovative project.Methodology: Within the context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
1
0
2
Order By: Relevance
“…In the meantime, some of the German model clinics have also employed PSW (37). A case study in the German town of Geesthacht demonstrated the transformative power of the GTB financing approach for enabling the introduction of peer-supported interventions (38). PSW are therefore very important in FIT models of both countries.…”
Section: Discussionmentioning
confidence: 99%
“…In the meantime, some of the German model clinics have also employed PSW (37). A case study in the German town of Geesthacht demonstrated the transformative power of the GTB financing approach for enabling the introduction of peer-supported interventions (38). PSW are therefore very important in FIT models of both countries.…”
Section: Discussionmentioning
confidence: 99%
“…Im letzteren Fall können die Umstrukturierungen weitreichend sein, wie die Modellprojekte in SH zeigen, z. B. in Itzehoe, Heide und Geesthacht, die oft auf lange Laufzeiten und Entwicklungen im Rahmen von Vorläufermodellen aufbauen 19 , 35 .…”
Section: Diskussionunclassified
“…Durch diese Umstrukturierung wurden Ressourcen freigesetzt, die in verschiedene Formen der aufsuchenden Behandlung, der Wohntherapie (Housing First [15]) und der unterstützten Beschäftigung sowie in die Förderung der sektorübergreifenden Zusammenarbeit reinvestiert wurden [16]. Es entstand ein komplexes und umfassendes Netzwerk von Einrichtungen innerhalb und außerhalb des Krankenhauses, das verschiedene gemeinnützige Organisationen, ehrenamtliche Netzwerke, kooperierende Arztpraxen, ambulante Zentren, häusliche Behandlungsteams und Formen von Peer-organisierten Unterstützungsformen einschloss.…”
Section: Das Geesthachter Modellunclassified